2017
DOI: 10.1371/journal.pone.0188081
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced eicosapentaenoic acid production by a new deep-sea marine bacterium Shewanella electrodiphila MAR441T

Abstract: Omega-3 fatty acids are products of secondary metabolism, essential for growth and important for human health. Although there are numerous reports of bacterial production of omega-3 fatty acids, less information is available on the biotechnological production of these compounds from bacteria. The production of eicosapentaenoic acid (EPA, 20:5ω3) by a new species of marine bacteria Shewanella electrodiphila MAR441T was investigated under different fermentation conditions. This strain produced a high percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
(86 reference statements)
1
10
0
Order By: Relevance
“…Given the presence of two discrete pathways for the biosynthesis of unsaturated fatty acids, we hypothesized that genes critical for MUFA synthesis could be disrupted in the native producing organism and compensated for by PUFA produced by the Pfa synthase. Previous work utilizing the fatty acid biosynthesis inhibitor cerulenin ( 7 , 20 ) or genetic disruption of the fabF gene, which encodes the key condensing enzyme, β-ketoacyl-ACP (acyl carrier protein) synthase II, involved in 18:1 production ( 9 ), showed that compensatory increases in PUFA content mitigated the loss of MUFA biosynthesis in the marine bacterium Photobacterium profundum SS9. Additionally, transposon screening for pressure-sensitive mutants of P. profundum SS9 revealed that fabB was not an essential gene and that its disruption led to a pressure-sensitive phenotype ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the presence of two discrete pathways for the biosynthesis of unsaturated fatty acids, we hypothesized that genes critical for MUFA synthesis could be disrupted in the native producing organism and compensated for by PUFA produced by the Pfa synthase. Previous work utilizing the fatty acid biosynthesis inhibitor cerulenin ( 7 , 20 ) or genetic disruption of the fabF gene, which encodes the key condensing enzyme, β-ketoacyl-ACP (acyl carrier protein) synthase II, involved in 18:1 production ( 9 ), showed that compensatory increases in PUFA content mitigated the loss of MUFA biosynthesis in the marine bacterium Photobacterium profundum SS9. Additionally, transposon screening for pressure-sensitive mutants of P. profundum SS9 revealed that fabB was not an essential gene and that its disruption led to a pressure-sensitive phenotype ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the study of Dailey et al (), wherein the authors recovered numerous red bacterial colonies on TTC plates while plating the broth cultures of fish intestine samples. The highest TPC and putative omega‐3 producers were recorded for samples collected from station K6 with a depth of 11 m. Generally, omega‐3 fatty acid producing bacteria were predominately isolated from sediment and fish intestines samples collected from Ocean depths (Akimoto et al, ; Bianchi et al, ; Zhang and Burgess, ); however, reports of isolation from shallow temperate waters are also available (Shulse and Allen, ). In this study from subtropical area, the putative omega‐3 producers count were higher in samples collected at 11 m than at 32 m depth.…”
Section: Resultsmentioning
confidence: 99%
“…The reported levels in the present study also fall into mid‐ or low‐level category. Several authors have attempted to optimize the media and growth conditions and reported higher levels of EPA up to 40% of TFAs at the standardized conditions (Akimoto et al, ; Yazawa, ; Cho and Mo, ; Zhang and Burgess, ). Hence, a detailed molecular characterization is required to find out the mechanism of EPA production by these isolates which were negative for all three of these genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain barophilic and psychrophilic organisms found in the ocean depths, such as members of the Shewanella genus, have been demonstrated to be substantial PUFA producers ( 133 ). Shewanella electrodiphila MAR441 was found to produce more EPA after being supplemented with cerulenin (FAS inhibitor) ( 134 ). In Shewanella species PKS-like gene clusters were identified for EPA biosynthesis that was successfully expressed in E. coli to produce EPA ( 135 ).…”
Section: Metabolic Engineering Of Existing Microbesmentioning
confidence: 99%